Тайные монгольские погребения (по материалам францисканской миссии 1245 года) - Юрченко, А.Г. (Степи Европы в эпоху средневековья, 2008)
Reports of the Franciscan mission of 1245 deal with the burial ceremony of the military elite of the Mongol Empire. There were three types of the mortuary ceremony: the burials of junior officers, the burials of senior officers, and those of the Chingisids. The overwhelming archaeological evidence of the 13th-14th cc. has no correspondence with the medieval records. This means that it was the secrets of the Mongol Empire but not the ordinary life of rank and file nomads that inspired a great interest between the Franciscans. The Soviet archaeology had not found any traces of the Mongol secret burials and thus declared that the “Mongols” took a minimal part in the cultural life of the Golden Horde. This statement is based on complete misunderstanding as to the meaning of the term “Mongols”, a polytonym which implied the whole ethnic mosaics of the Empire.